Pattern of Use and Outcomes with Hydromorphone Hydrochloride in Patients with Chronic Pain Across Several Medical Specialties: a Real-World Study - Francisco Villegas Estévez; María Dolores López Alarcón (Medical – Clinical – Research, 2026)
Background: Research on hydromorphone is limited. This study aimed to describe the pattern of hydromorphone hydrochloride use and the associated clinical outcomes in clinical practice across several medical specialties. Methods: This was an observational, retrospective, descriptive multicenter study. To be included in the study, individuals had to be outpatients, aged ≥ 18 years, diagnosed with chronic pain lasting at least 3 months, and with a score ≥4 on a numerical rating scale. We recorded information on the structure, process, and outcome indicators. Except for the structural indicators, we used aggregated data. Aggregated data are presented as the mean and 95% confidence interval of the aggregated mean (‘mean’) or aggregated percentage (‘mean percentage’). Results: A total of 84 specialists included aggregated data from 840 patients. A mean of 52.9% (95% CI, 46.8–58.9) of the patients were categorized as frail, and the patients received a mean of 6.1 (95% CI, 5.4-6.9) treatments. Most patients were treated for chronic non-cancer pain (mean 47%, 95% CI39.6–54.5), followed by cancer pain (mean 29.6%, 95% CI 21.3–38.0) and exacerbated chronic pain (mean 23.3%, 95% CI 18.1–28.6). The most common reason for hydromorphone prescription was that previous treatment was ineffective (mean 53.7%, 95% CI 46.3–61.0). Pain control was achieved by 71.3% of patients and adequate sleep by 66.1% of patients, without significant differences across specialties. Conclusion: Our results support that hydromorphone under routine clinical practice conditions is effective for the management of chronic pain with relevant improvement of pain intensity and sleep across several specialties involved in the management of these patients, regardless of the presence of frailty and polypharmacy.